Hydrogel Contact Lens for Extended Delivery of Ophthalmic Drugs - Xiaohong Hu; Lingyun Hao; Huaiqing Wang; Xiaoli Yang; Guojun Zhang; Guoyu Wang; Xiao Zhang (International Journal of Polymer Science)
Soft contact lenses can improve the bioavailability and prolong the residence time of drugs and, therefore, are ideal drug carriers for ophthalmic drug delivery. Hydrogels are the leading materials of soft contact lenses because of their biocompatibility and transparent characteristic. In order to increase the amount of load drug and to control their release at the expected intervals, many strategies are developed to modify the conventional contact lens as well as the novel hydrogel contact lenses that include (i) polymeric hydrogels with controlled hydrophilic/hydrophobic copolymer ratio; (ii) hydrogels for inclusion of drugs in a colloidal structure dispersed in the contact lenses; (iii) ligand-containing hydrogels; (iv) molecularly imprinted polymeric hydrogels; (v) hydrogel with the surface containing multilayer structure for drugs loading and releasing. The advantages and disadvantages of these strategies in modifying or designing hydrogel contact lenses for extended ophthalmic drug delivery are analyzed in this paper.